2013
DOI: 10.4314/jab.v65i0.89579
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and potential for aflatoxin contamination in groundnuts and peanut butter from farmers and traders in Nairobi and Nyanza provinces of Kenya

Abstract: Objective: Most of the peanut butter marketed in Nairobi is processed in cottage industry and its aflatoxin contamination status has not been documented. This study was therefore conducted to determine the status of aflatoxin contamination in groundnuts and peanut butter in Nairobi and Nyanza. Methodology and results: Eighty two fresh samples comprising raw and roasted groundnuts and peanut butter were obtained from market outlets and cottage processors in Nairobi and Nyanza regions. The marketers and processo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
1
20
1
1
Order By: Relevance
“…Of the 18 samples tested, only 3 had detectable levels of aflatoxin, ranging from 7 to 620 μg/kg. In east Africa, Ndung'u et al (2013) tested 82 fresh and roasted samples from markets in Kenya located in Nyanza and Nairobi. They found that 43% of the samples were above Kenya's regulatory limit of 10 μg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 18 samples tested, only 3 had detectable levels of aflatoxin, ranging from 7 to 620 μg/kg. In east Africa, Ndung'u et al (2013) tested 82 fresh and roasted samples from markets in Kenya located in Nyanza and Nairobi. They found that 43% of the samples were above Kenya's regulatory limit of 10 μg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 43% of the samples were above Kenya's regulatory limit of 10 μg/kg. Ndung'u et al (2013) reported that groundnut kernels that was sorted had the highest proportion of samples (83%) with aflatoxin levels below 10 μg/kg. Therefore, they proposed that sorting should be made mandatory for the groundnut marketers with effective monitoring to ensure compliance and that punitive measures should be given to non-compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Contamination of groundnut and groundnut-based products by aflatoxins has extensively been reported in tropical countries where this crop is largely cultivated (Gachomo et al 2004;Ogunsanwo et al 2004;Bankole et al 2005;Aliyu and Kutama 2007;Ngoko et al 2008;Mutegi et al 2009;Soler et al 2010;Ndung'u et al 2013;Nyirahakizimana et al 2013;Limbikani et al 2014), but only very few studies focused on both aflatoxigenic moulds and aflatoxins (Gachomo et al 2004;Aliyu and Kutama 2007;Ngoko et al 2008;Soler et al 2010;Ndung'u et al 2013;Nyirahakizimana et al 2013). In Nigeria, groundnut is mostly consumed in its processed form (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…the marketing sectors especially at retail level in traditional market; here the contamination was generally found to be the highest. This indicates that aflatoxin contaminated peanuts entered in the marketing chain, post-harvest contamination of aflatoxin build up due to poor storage conditions (Dharmaputra et al, 2003;Dharmaputra et al, 2004;Rahmianna et al, 2007;Ndung'u 2013).…”
Section: Introductionmentioning
confidence: 99%